2003
DOI: 10.1292/jvms.65.1003
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing for Canine Artificial Insemination with Frozen Semen and Parentage Testing by Microsatellite Markers in Superfecundency

Abstract: ABSTRACT. Parentage testing was performed in sixteen litters by canine artificial inseminations with frozen semen from different sires on Days 5 and 7 after the LH surge. It became apparent that only 25% of dams had superfecundation, but 43.8% of dams were whelped after insemination only on Day 5 after the LH surge and 31.3% of dams after insemination only on Day 7. Of the total 87 puppies , 46% were born after insemination on Day 5 after the LH surge and 54% after insemination on Day 7. This result strongly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
2
14
0
Order By: Relevance
“…Of 13 males, 6 males exhibited severely poor fertility (less than 20% pregnancy rate) and 3 males exhibited high fertility (over 70% pregnancy rate) on artificial insemination. Since the optimal time for insemination with frozen semen theoretically appeared to be around day 4 after the LH surge [9], and it has been suggested that artificial insemination with frozen semen is successful on days 4 and 6 [10], and days 5 and 7 [11,12] after the LH surge in canine species, we thus performed transcervical insemination between days 4 and 8 after the estimated LH surge in the Labrador Retriever. However, as shown in Table 2, heterospermic insemination in the present study revealed the optimal timing for transcervical artificial insemination with frozen-thawed semen to be by day 6 after the estimated LH surge.…”
Section: Resultsmentioning
confidence: 99%
“…Of 13 males, 6 males exhibited severely poor fertility (less than 20% pregnancy rate) and 3 males exhibited high fertility (over 70% pregnancy rate) on artificial insemination. Since the optimal time for insemination with frozen semen theoretically appeared to be around day 4 after the LH surge [9], and it has been suggested that artificial insemination with frozen semen is successful on days 4 and 6 [10], and days 5 and 7 [11,12] after the LH surge in canine species, we thus performed transcervical insemination between days 4 and 8 after the estimated LH surge in the Labrador Retriever. However, as shown in Table 2, heterospermic insemination in the present study revealed the optimal timing for transcervical artificial insemination with frozen-thawed semen to be by day 6 after the estimated LH surge.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, there is a strong, positive, linear correlation between the interval since the LH peak and the stage of embryonic development, with the first potentially fertilised oocytes and zygote identified 7 d after the LH peak (Bysted et al, 2001). In the light of the findings by Nöthling et al (2003) and Tsumagari et al (2003), this synchrony suggests a need to more closely compare the fertility of Days 5, 6 and 7 after PPC first reaches a value between 6 and 9 nmol/L. Some dog breeders believe that the time of mating or the time of artificial insemination has an effect on the gender ratio of the resulting litters.…”
Section: Inseminatedmentioning
confidence: 94%
“…Their bitches yielded mean litter sizes of 4 ± 2.4 (SD), 6.6 ± 2.5 and 6.5 ± 2.5 from the inseminations done 5, 7 and 5 and 7 days after PPC exceeded 6 nmol/L, respectively; suggesting that good fertility is possible from inseminations done 7 days after PPC first exceeded 6 nmol/L. Unfortunately, the study by Tsumagari et al (2003) does not permit a comparison between the fertility of inseminations done on either Day 5 or Day 7 with those done on Day 6. Tsutsui (1975) and Bysted et al (2001) showed that embryonic development is synchronized among embryos within a bitch, suggesting that fertilization occurs over a short period of time within a bitch.…”
Section: Inseminatedmentioning
confidence: 96%
See 2 more Smart Citations